2004
DOI: 10.1124/dmd.32.7.734
|View full text |Cite
|
Sign up to set email alerts
|

LIPOPOLYSACCHARIDE-MEDIATED REGULATION OF HEPATIC TRANSPORTER mRNA LEVELS IN RATS

Abstract: ABSTRACT:The function of hepatic transporters is to move organic substances across sinusoidal and canalicular membranes. During extrahepatic cholestasis, transporters involved in the movement of substances from blood to bile, such as sodium/taurocholate-cotransporting polypeptide (Ntcp) and multidrug resistance protein 2 (Mrp2), are down-regulated, whereas others that transport chemicals from liver to blood, such as Mrp3, are up-regulated. Unlike extrahepatic cholestasis, where transporter expression responds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
88
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 39 publications
14
88
2
Order By: Relevance
“…The present data confirm previous reports that demonstrated the ability of LPS to down-regulate mRNA levels of the sinusoidal uptake transporters Oatp1, Oatp2, Ntcp, and Oatp4 in mouse and rat liver (Trauner et al, 1998;Geier et al, 2003;Cherrington et al, 2004;Siewert et al, 2004). Furthermore, the present study illustrates the fact that Oat2 mRNA levels in liver tend to decrease after LPS administration, which is similar to the observation in rats (Cherrington et al, 2004). Our data also demonstrated that LPS decreased mRNA levels of Bsep and Mrp2 in mouse liver.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The present data confirm previous reports that demonstrated the ability of LPS to down-regulate mRNA levels of the sinusoidal uptake transporters Oatp1, Oatp2, Ntcp, and Oatp4 in mouse and rat liver (Trauner et al, 1998;Geier et al, 2003;Cherrington et al, 2004;Siewert et al, 2004). Furthermore, the present study illustrates the fact that Oat2 mRNA levels in liver tend to decrease after LPS administration, which is similar to the observation in rats (Cherrington et al, 2004). Our data also demonstrated that LPS decreased mRNA levels of Bsep and Mrp2 in mouse liver.…”
Section: Discussionsupporting
confidence: 81%
“…These include Ntcp, Bsep, Oatp1, Oatp11, Mrp1, and Mrp9. The ability of LPS to down-regulate Ntcp, Oatp1, and Bsep mRNA expression has been demonstrated previously in vivo in rats and mice (Trauner et al, 1998;Hartmann et al, 2002;Geier et al, 2003;Cherrington et al, 2004;Siewert et al, 2004;Geier et al, 2005). The current results in IL-6(Ϫ/Ϫ) mice also confirm a previous report in which LPS administration resulted in transcriptional down-regulation of Ntcp, Bsep, and Oatp1 that was equally robust in WT and IL-6(Ϫ/Ϫ) mice (Siewert et al, 2004).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations